Preparation of future social workers to work with parents raising children with autic disorders - Polishchuk , Vira (Social work and education, 2022)
The article highlights the problem of professional training of future social workers for social support of families raising children with various manifestations of autistic disorders, as an important area of their professional activity. It was found that in order to successfully solve the problem, the training of future social workers should be considered as a complex integrative process based on students’ motivation for this activity; systematic knowledge of family social work; skills and abilities that underlie the performance of professional functions and tasks for the implementation of family-oriented practices of supporting families raising children with autism. The article reveals the potential of the educational program for higher education of the first (Bachelor’s) level in the field of knowledge 23 "Social Work" Specialty 231 "Social Work" to work with family members raising children with autism. It is proved that a meaningful search for improvement of the educational program and effective ways to organize the educational process of training relevant specialists should be carried out on the basis of a systematic approach, the main purpose of which is to form in future professionals theoretical knowledge, skills and competent skills. The article reveals the experience of teachers of the Department of Social Work and Management of Socio-Cultural Activities of Ternopil V. Hnatiuk National Pedagogical University on the theoretical and practical components of training future professionals to carry out diverse social work with families, including working with parents and other members. families raising children with autism.